The Apollo 11 moon landing - Engdahl, Sylvia (Perspectives on modern world history, 2011)
"The Apollo 11 Moon Landing: Historical Background on the Apollo 11 Moon Landing; Controversies Surrounding the Apollo 11 Moon Landing; Personal Narratives"-- Provided by publisher